Contained Testing: Comparison of Scientific Literacy Ability of Middle and High School Students Aged 15 Years Old - Prafitasari, Aulya Nanda; Pradhana, Restasa Britan (Science Education and Application Journal, 2023)
One of skills used as the basic of high order thinking skills is scientific literacy ability. This ability is evaluated by OECD in PISA program follow by students aged 15 years old from various countries. Therefore, this article is amied to compare scientific literacy ability of middle and high school students aged 15 years old on a limited scale.Â  Scientific literacy ability has 4 indicators which are nominal literacy, functional literacy, conceptual/procedural literacy, and multi-dimensional literacy. The data were gained from the comparison between 25 students grade IX SMP Negeri 7 Jember and 25 students grade X SMA Negeri 2 Situbondo. The data were analyzed using Kruskal Wallis with SPSS program. The result showed that 3 among 4 indicators of scientific literacy test of middle and high school students aged 15 years old had sig >0.05, which means there is no significant difference. Those 3 indicators are nominal literacy (0.204), functional literacy (0.107), and conceptual/procedural literacy (0.154). Meanwhile, for multi-dimensional literacy showed sig 0.04 or <0.05, hence it can be concluded that there is significant difference of multi-dimensional literacy ability between middle and high school students aged 15 years old.